2015
DOI: 10.1590/2237-6089-2014-0043
|View full text |Cite
|
Sign up to set email alerts
|

Profile and pattern of crack consumption among inpatients in a Brazilian psychiatric hospital

Abstract: Introduction: Crack cocaine use is associated with polydrug abuse, and inpatients dependent on crack exhibit profiles of serious consumption patterns. Use of alcohol and tobacco and other drugs is a risk factor for experimentation of additional drugs, including crack cocaine.Objectives:The present study describes the characteristics and crack consumption patterns among inpatients in treatment during 2011 and 2012 at the Hospital Psiquiátrico São Pedro (Porto Alegre, Brazil). An additional objective was to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
1
4
0
10
Order By: Relevance
“…The multiple drug use found in the sample corroborates the findings of other studies (23)(24) , in which a trend of multiple drug use as observed in hospitalized individuals for the treatment of alcoholism (23) . In those hospitalized for crack addiction, involvement with legal drugs was observed during adolescence (24) .…”
Section: Discussionsupporting
confidence: 90%
“…The multiple drug use found in the sample corroborates the findings of other studies (23)(24) , in which a trend of multiple drug use as observed in hospitalized individuals for the treatment of alcoholism (23) . In those hospitalized for crack addiction, involvement with legal drugs was observed during adolescence (24) .…”
Section: Discussionsupporting
confidence: 90%
“…[4][5][6] The profile of crack users is generally young adults who are users of multiple PS, but adopt crack as their drug of choice. [7][8][9] The most common pattern of crack consumption described in the literature is characterized by loss of control, seeking behavior (despite obvious harm to various aspects of life), intense craving, and frequent relapses. 10 These characteristics are associated with changes to neural circuits that manage behavioral processes, such as reward and conditioning behaviors;…”
Section: Introductionmentioning
confidence: 99%
“…However, eight studies were excluded because they did not meet the inclusion In response, it was decided to use the term "cocaine and/or crack users", since the majority of study samples comprised users of multiple PS, which is consistent with the profile generally described in the literature. [7][8][9] With relation to the instruments employed to evaluate inhibitory control, the majority of these instruments use Table 3 lists the instruments used in the articles reviewed and the frequency of use.…”
Section: Introductionmentioning
confidence: 99%
“…The rst experience with crack cocaine usually occurs in the transition to adulthood, often following the exposure to alcohol, tobacco, marijuana and snorted cocaine 10,11 . The age of onset of consumption is in uenced by numerous combinations of protective and risk factors, within a system that integrates social environments, relationship groups, individual characteristics and behavioral patterns 11,12 .…”
Section: Introductionmentioning
confidence: 99%